ASUPAN ORAL INADEKUAT, PERUBAHAN NILAI LABORATORIUM, PERILAKU SALAH TENTANG MAKANAN PADA PASIEN CHRONIC KIDNEY DISEASE - Mahesa Dwipayani, Ni Kadek; Fadhilah, Zulfa Rizki; Isdiany, Nitta (Jurnal Gizi dan Dietetik, 2023)
Background: Chronic Kidney Disease (CKD) is a disease that attacks the kidneys and the condition gradually worsens, becomes chronic or persistent, and lasts a long time. The prevalence of chronic kidney disease cases in Indonesia according to basic health research (Riskesdas) in 2018 was 0.38%. Hypertension is one of the risk factors often found in kidney failure. Prolonged increase in blood pressure in arterioles and glomeruli will cause sclerosis of blood vessels. Case: Mr.U aged 50 years experienced nutritional problems inadequate oral intake, changes in urea and creatinine values, and wrong behavior about food during hospitalization patient's medical diagnosis are CKD and hypertension. Results and Discussion: Providing an initial low protein diet of 0.6 and then at the end of treatment to high energy high protein on HD 1.2 gr/kg ideal body weight in a soft form adapted to the patient's ability has purpose to increase patient intake. The dietary requirements given at the beginning of the intervention were energy 2047.5 kcal, protein 35.1 g, fat 68.25 g, carbohydrates 323.5 g. The results of monitoring and evaluation showed that during observation on the third day, the patient's energy intake reached 75%. The results of urea and creatinine also decreased, physical/clinical showed reduced tightness but still experienced post-hemodialysis nausea. Collaboration was carried out together with doctor, nutritionists, nurses, and waiters. During the intervention, education, and counseling were also provided regarding the patient's eating arrangements. Conclusion: the intervention provided can overcome some of the patient's nutritional problems.